The life and philosophy of Śrīśaṅkara - Jayanthy, S (New Bharatiya Book Corporation, 2017)
Study of the Bhagavatpādamahimānuvarṇana, work on Śaṅkarācārya and his philosophy by Bālagopālayatīndra, 18th century Sanskrit author ; includes Sanskrit text